ANALYSIS OF THE CALCULATION OF PRODUCTION COSTS AND SELLING PRICES IN UD. BINA USAHA BAGUSARI - Sugiarti, Juniar; Sochib, Sochib; Eka Pratiwi, Yanna (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2020)
Business (company) is an organization that provides a variety of goods or services for sale with the aim of obtaining profits. Accounting calculations on companies are needed at the production price and selling price at a company. In this case then direct this research in the calculation of production prices and selling prices. The data needed in this study can be obtained through documentation and field research. The data obtained in this analysis uses the Descriptive Quantitative method, based on the analysis shows that the calculation of production costs and selling prices using the calculation method carried out by the UD with the calculation of production costs using the variable costing method is lower than the calculations made by the company. Because the variable costing method calculates the variable costs associated with the production process and selling prices while the calculation method applied by the company lists all costs including variable overhead costs and fixed overhead costs. So that there is a difference in production costs and selling prices according to company methods and variable costing methods.